PENGARUH PELATIHAN SADAR MAKAN IKAN TERHADAP PENINGKATAN PENGETAHUAN, SIKAP, PRAKTIK DAN ASUPAN GIZI IBU DAN ANAK BALITA - M. Zen . Rahfiludin; Cahya Tri Pumami; Tinuk . Istiarti (Universitas Muhammadiyah Semarang, 2004)
ABSTRACT Background: Indonesia is a country with high potential on fish producing but lack consuming of it. The training of realization in consuming fish is considered to give knowledge, attitude and practice to the mother in consuming fish for her family. Objectives: to discover the differences on knowledge, attitude and practice in consuming fish of the mother which has children 3-5 years old in which given training in cooking fish and with those who only receive the information. Method; this training is including quasi experimental by using pretest posttest control group design. This research takes place in two